The Impact of Cultural Differences on Management of Global ERP Implementation Projects: Case Valmet - Voutilainen, Leevi (2024)
The objective of this study was to examine the impact of cultural differences and to identify solutions to challenges they cause in multinational ERP projects, with a particular focus on project management and financial management. While ERP implementations have been extensively researched over the past decades, studies addressing specifically the effects of cultural differences remain limited. Particularly case studies including multiple countries have been relatively rare. This master’s thesis began with a literature review, which provided the basis for a qualitative case study. The theoretical framework was constructed using Geert Hofstede’s dimensions of national culture and a selection of the most cited critical success factors (CSFs) in ERP literature. The study was conducted as an assignment for the Finnish multinational corporation Valmet, focusing on the company’s global ERP program Leap Forward. The research examined ERP implementations in the selected target countries China and the United States by interviewing individuals who had participated in ERP projects in these countries. More than half of the interviewees had been involved in ERP projects in both target countries, enabling not only a detailed analysis of each country but also a comparison of the two cultures. The findings highlight the influence of cultural differences on multinational ERP projects. Additionally, the study revealed the remarkable cultural differences between China and the United States and their impact on ERP implementations. As an example, the best practices for change management differed considerably between the two countries: in China top management was the primary target for change management, whereas in the United States, change management was important to implement at all levels of the organization. The results of this research highlight the importance of including cultural considerations into multinational ERP projects.